若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6,则m= n=若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6,则m= n=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 04:06:50
若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6,则m=n=若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6
若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6,则m= n=若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6,则m= n=
若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6,则m= n=
若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6,则m= n=
若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6,则m= n=若(x²-1)(x²+mx+n)=x的3次方-6x²+11x-6,则m= n=
(x-1)((x²+mx+n)=x³+mx²+nx-x²-mx-n=x³+(m-1)x²+(n-m)x-n=x³-6x²+11x-6
所以n=6,m=-5